2011
DOI: 10.1016/j.ajpath.2011.02.030
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Invasion of Head and Neck Squamous Cell Carcinoma Cells Does Not Require Macrophages

Abstract: Invasion of tumor cells into the local stroma is an important component in cancer progression.Here we report studies of the in vivo invasion of head and neck squamous cell carcinoma (HNSCC) cells in response to applied gradients of a growth factor [epidermal growth factor (EGF)] and a chemokine (CXCL12), using orthotopic floor-of-mouth models. Analysis of the invading cells indicated that >75% of them were tumor cells, about 15% macrophages, and <10% were unidentified. Surprisingly, although macrophages invade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
0
12
0
2
Order By: Relevance
“…In conjunction with the fact that EGF was expressed less in T than in A, existence of grow supporting mechanisms of tumour cells by tumour-adjacent tissues can be assumed. It was also found that EGF gradients could direct invasion into surrounding tissues [57]. Van Limbergen et al observed that FLT1 increased expression in the tumour tissue as compared with the normal epithelium [54], but we found no significant differences between FLT1 expression in tumour, tumour-adjacent tissues or tonsillectomies.…”
Section: Discussionmentioning
confidence: 76%
“…In conjunction with the fact that EGF was expressed less in T than in A, existence of grow supporting mechanisms of tumour cells by tumour-adjacent tissues can be assumed. It was also found that EGF gradients could direct invasion into surrounding tissues [57]. Van Limbergen et al observed that FLT1 increased expression in the tumour tissue as compared with the normal epithelium [54], but we found no significant differences between FLT1 expression in tumour, tumour-adjacent tissues or tonsillectomies.…”
Section: Discussionmentioning
confidence: 76%
“…Crystal structure of the EGFR protein (PDB id: 1M17) was retrieved from PDB databank (http://www.pdb.org/) [3,9,11]. The optimization of protein as well as inhibitors was carried out using UCSF Chimera software, implying amber parameters, followed by minimization with MMTK method in 500 steps with a step size of 0.02 Å (www.cgl.ucsf.edu/ chimera/) [9].…”
Section: Selection and Preparation Of Macromoleculementioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) is a cell-surface receptor tyrosine kinase (RTK) belonging to the epidermal growth factor family (EGF-family). It is unidirectionally transactivated through CXCR4 in HNSCC cells [3]. EGFR driven signalling pathway in HNSCC is predominantly responsible for the malignant features of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Morphologische Studien an HNSCC konnten zeigen, dass das Muster der Invasion, eine perineurale Invasion und die Prä-sens von Entzündungszellen mit dem klinischen Verlauf korrelieren [ 85 ] . Bei HNSCC liegt häufi g EGFR (epidermal growth factor receptor) verstärkt exprimiert vor.…”
Section: Invasion Und Metastasierungunclassified
“…Neben dem stimulierenden Einfl uss von EGFR auf die Proliferation von Zellen verfügt EGFR auch über die Fähigkeit die Invasion von Tumorzellen zu fördern, indem die zelluläre Mobilität verstärkt wird. Dies konnte in vitro bereits für HNSCC-Zellen gezeigt werden [ 86 ] und in einer kürzlich erschienenen Studie konnte im Tiermodell in vivo bestätigt werden, dass der Ligand von EGFR (EGF) und das Chemokin CXCL12 die Invasion bei HNSCC induziert [ 85 ] . Im weiteren Verlauf des Wachstums wird ab einer bestimmten Größe des Tumors sowohl für die Sauerstoff versorgung, als auch für die Entsorgung von Abfallprodukten des Stoff wechsels eine eigene Blutversorgung erforderlich.…”
Section: Invasion Und Metastasierungunclassified